2019
DOI: 10.1088/1742-6596/1390/1/012091
|View full text |Cite
|
Sign up to set email alerts
|

On Firewalls in quantum-corrected General Relativity

Abstract: We consider the information loss paradox at different angles, from the standard semi-classical approximation of General Relativity to the recently proposed scenarios of black holes evolution caused by effects of gravity quantization. Focusing on the Firewall proposal, we study the loop effects on the geometry and boundary conditions in black hole spacetimes and analyze the energy measured by an infalling observer near their horizons. As a result we obtain a trans-Planckian energy transition for the time-depend… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Looking at Figure 4 with the results of numerics for the spherically symmetric (Schwarzschild) background (which reproduce in part data in Figures 2 and 8 of Ref. [43]), one may notice that: For the distorted BH background (15) with the metric potential (40), the deformation parameters of which are chosen to be b = 1 and a = 1 + α = 1 + 0.2, putting the data for the same type of waves on plots, we encounter important differences in compare to the previously considered cases (see Figure 5). We observe that:…”
Section: The Grey-body Factor: Schwarzschild Vs Distorted Schwarzschildmentioning
confidence: 54%
See 3 more Smart Citations
“…Looking at Figure 4 with the results of numerics for the spherically symmetric (Schwarzschild) background (which reproduce in part data in Figures 2 and 8 of Ref. [43]), one may notice that: For the distorted BH background (15) with the metric potential (40), the deformation parameters of which are chosen to be b = 1 and a = 1 + α = 1 + 0.2, putting the data for the same type of waves on plots, we encounter important differences in compare to the previously considered cases (see Figure 5). We observe that:…”
Section: The Grey-body Factor: Schwarzschild Vs Distorted Schwarzschildmentioning
confidence: 54%
“…Technically, we would like to extend the known Regge-Wheeler-Zerilli [70,71] equations for small d-wave perturbations over the background (15) and to solve them. First step on this way is to separate the variables in the corresponding relativistic spin equation.…”
Section: Basic Equations and Separation Of Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although quantum gravitational effects (reviews of various approaches to quantization of a matter-gravity system can be found, e.g., in [1][2][3][4][5]) are often set aside, it has become increasingly clear through a series of recent works [6][7][8][9][10][11][12][13][14][15][16][17][18][19] that they are crucial for solving some of the outstanding problems in theoretical and astro-theoretical physics. For instance, they have proven to be indispensable for precisely formulating (and potentially solving) the black hole information paradox [6][7][8]20].…”
Section: Introductionmentioning
confidence: 99%